Combined Cytological and Transcriptomic Analysis Reveals a Nitric Oxide Signaling Pathway Involved in Cold-Inhibited Camellia sinensis Pollen Tube Growth - Wang, Weidong; Sheng, Xianyong; Shu, Zaifa; Li, Dongqin; Pan, Junting; Ye, Xiaoli; Chang, Pinpin; Li, Xinghui; Wang, Yuhua (Frontiers in Plant Science, 2016)
Nitric oxide (NO) as a signaling molecule plays crucial roles in many abiotic stresses in plant development processes, including pollen tube growth. Here, the signaling networks dominated by NO during cold stress that inhibited Camellia sinensis pollen tube growth are investigated in vitro. Cytological analysis show that cold-induced NO is involved in the inhibition of pollen tube growth along with disruption of the cytoplasmic Ca2+ gradient, increase in ROS content, acidification of cytoplasmic pH and abnormalities in organelle ultrastructure and cell wall component distribution in the pollen tube tip. Furthermore, differentially expressed genes (DEGs)-related to signaling pathway, such as NO synthesis, cGMP, Ca2+, ROS, pH, actin, cell wall and MAPK cascade signal pathways, are identified and quantified using transcriptomic analyses and qRT-PCR, which indicate a potential molecular mechanism for the above cytological results. Taken together, these findings suggest that a complex signaling network dominated by NO, including Ca2+, ROS, pH, RACs signaling and the crosstalk among them, is stimulated in the C. sinensis pollen tube in response to cold stress, which further causes secondary and tertiary alterations, such as ultrastructural abnormalities in organelles and cell wall construction, ultimately resulting in perturbed pollen tube extension.